2019
DOI: 10.31557/apjcp.2019.20.11.3487
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Benzo[D]Thiazole with Dimethylpyrazol Derivatives

Abstract: A series of new benzothiazole derivatives containing dimethylpyrazole were synthesized and evaluated for their anticonvulsant activity, neurotoxicity and cytotoxicity by using the maximal electroshock (MES), rotarod neurotoxicity (TOX) and MTT colorimetric assay. Among the compounds studied, four compounds (6a, 6b, 6g and 6m) showed better anticonvulsant than the others at 300 mg/kg and they also showed anticonvulsant activity at the dose of 100 mg/ kg. All the synthetic compounds showed lower neurotoxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…[87] Furthermore, EVs from murine GL261 glioma cells have shown to promote tumor growth by inhibiting CD8+ T-cells. [88] More recently, van der Vos et al demonstrated that GBM-derived EVs transfer functional RNA to microglia/macrophages in the brain. Exposure of microglia to GBM-EVs lead to downregulation of miR-21/miR-451 target c-Myc mRNA.…”
Section: Evs and The Tumor Microenvironmentmentioning
confidence: 99%
“…[87] Furthermore, EVs from murine GL261 glioma cells have shown to promote tumor growth by inhibiting CD8+ T-cells. [88] More recently, van der Vos et al demonstrated that GBM-derived EVs transfer functional RNA to microglia/macrophages in the brain. Exposure of microglia to GBM-EVs lead to downregulation of miR-21/miR-451 target c-Myc mRNA.…”
Section: Evs and The Tumor Microenvironmentmentioning
confidence: 99%